2014
DOI: 10.1257/pol.6.4.302
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline Taxes and Consumer Behavior

Abstract: Gasoline taxes can be employed to correct externalities associated with automobile use, to reduce dependency on foreign oil, and to raise government revenue. Our understanding of the optimal gasoline tax and the efficacy of existing taxes is largely based on empirical analysis of consumer responses to gasoline price changes. In this paper, we directly examine how gasoline taxes affect consumer behavior as distinct from tax-exclusive gasoline prices. Our analysis shows that a 5-cent tax increase reduces gasolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
193
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(211 citation statements)
references
References 44 publications
(38 reference statements)
15
193
1
2
Order By: Relevance
“…Recent literature has found that gasoline consumption has a larger response to gasoline tax changes than it does to tax‐exclusive gasoline price changes (Li et al . [2014]; Rivers and Schaufele [2015]), and some evidence suggests that the demand for fuel economy may also respond more to gasoline tax changes (Li et al . [2014]).…”
Section: Estimation Results and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has found that gasoline consumption has a larger response to gasoline tax changes than it does to tax‐exclusive gasoline price changes (Li et al . [2014]; Rivers and Schaufele [2015]), and some evidence suggests that the demand for fuel economy may also respond more to gasoline tax changes (Li et al . [2014]).…”
Section: Estimation Results and Implicationsmentioning
confidence: 99%
“…[2014]; Rivers and Schaufele [2015]), and some evidence suggests that the demand for fuel economy may also respond more to gasoline tax changes (Li et al . [2014]). In our analysis, it would be interesting to explore whether fleet and retail buyers respond differently to gasoline tax changes compared to market price changes.…”
Section: Estimation Results and Implicationsmentioning
confidence: 99%
“…Li et al (2014) study the effect of changes in gasoline prices and gasoline taxes on consumption and find that consumers respond more strongly to gasoline tax changes. Li et al (2014) study the effect of changes in gasoline prices and gasoline taxes on consumption and find that consumers respond more strongly to gasoline tax changes.…”
Section: (Ii) Gst Revenuementioning
confidence: 99%
“…Li et al (2014) study the effect of changes in gasoline prices and gasoline taxes on consumption and find that consumers respond more strongly to gasoline tax changes. However, the findings of Li et al (2014) suggest that responses to tax changes may still be greater due to the strong coverage of tax changes in the media. First, consumers may be more sensitive to taxation because they consider tax changes to be more persistent than price changes.…”
Section: (Ii) Gst Revenuementioning
confidence: 99%
“…In the present empirical study, we aim to elucidate this challenge by examining whether the effectiveness of pro‐environmental tax incentives is affected by consumers' cognitive abilities. Indeed, research in economics and psychology has indicated that the cognitive salience of tax incentives (or, observability of tax information) affects consumer responses to those incentives (Chetty, Looney, & Kroft, 2009; Finkelstein, 2009; Li, Linn, & Muehlegger, 2012; Rivers & Schaufele, 2012). While focusing on comparing the overall salience of different tax incentives, however previous studies have not examined the influence that consumers' heterogeneous cognitive abilities may have on their reactions to a given tax incentive.…”
Section: Conceptual Developmentmentioning
confidence: 99%